PENGARUH LITERASI KEUANGAN, PEMBELAJARAN AKUNTANSI KEUANGAN, DAN GENDER TERHADAP KEMAMPUAN MENGELOLA KEUANGAN MAHASISWA AKUNTANSI - Desi Pita Lestari (2023)
A person's lack of understanding on how to manage finances causes the funds they have to be directed towards consumption needs, including excessive use of credit cards and not according to needs. This study aims to determine the effect of financial literacy, financial accounting learning, and gender on the ability to manage finances of accounting students. This study used a quantitative method with samples of S1 Accounting students at UPN "Veteran" Jakarta class of 2019 - 2021. The sampling technique used the Slovin equation with a total sample of 245 respondents. The data were processed and tested using descriptive statistical analysis methods, validity, reliability, normality, hypothesis, and multiple linear regression with the IBM SPSS 26 application. The results of this study indicate that financial literacy and financial accounting learning have a positive effect on the ability to manage finances of accounting students. Meanwhile, gender has no effect on the ability to manage accounting students' finances.